E-Real Estate Property Management System - Majid Shanto, Syed Nurul (2003)
Real estate business is one of the oldest businesses in the business world which is also considered to be associated with the toughest business environment to invest for investment because of its volatile behavior. In order to be competitive in the real estate market, the real estate developer as well as real estate specialist like real estate agent is constantly fighting for achieving marginal profit from the market. 21st century is the century of advance technology and utilizing its power in every possible business environment. Using technology in the real estate business environment is not a new concept but reaping full benefit from the technology by implementing, is yet to be achieved. This research is mainly focused on real estate business, its nature and its activities, but it also provides information about series of existing problems within the business environment which can be solved by implementing web enabled property management system “E-Real Estate”. E-Real Estate is not only a simple web solution for a real estate business but also addresses the future requirements of the next generation that finds the most suitable and safest place on earth. By using today’s technology and economic growth prediction may not be able to produce the best housing solution for tomorrow’s world, nevertheless, the system will satisfy the basic needs of the customer by implementing the fundamental information of real estate business which will not be changed even in future situation or growth of population.